The formation of higher alcohols in rice wine fermentation using different rice cultivars - Wang, Chunxiao; Yuan, Guoyi; He, Yulin; Tang, Jiadai; Zhou, Hongxiang; Qiu, Shuyi (Frontiers in Microbiology, 2022)
Higher alcohols are closely related to the flavor and safety of rice wine. The formation of n-propanol, isobutanol, isoamyl alcohol and phenylethanol during rice wine fermentations was for the first time investigated in this study among ten rice from two main production regions. Rice wine made from YS Yashui rice, the long grain non-glutinous rice from Guizhou, produced the highest yields of higher alcohols (487.45 mg/L), and rice wine made from five glutinous rice produced the lowest yields of higher alcohols (327.45 to 344.16 mg/L). An extremely strong correlation was found between the starch in rice and higher alcohols in rice wine. Further analysis first showed that the former fermentation period was key for the nutrient consumption and higher alcohols formation, with more than 55% of glucose being consumed and more than 75% of higher alcohols being synthesized in 48 h. Correlation analysis confirmed the strong correlation between nutrient consumption and higher alcohols formation including valine-isobutanol (coefficient higher than 0.8 in seven rice and higher than 0.6 in three rice), glucose-isoamyl alcohol (coefficient higher than 0.8 in five rice and higher than 0.6 in the other five rice), and glucose-phenylethanol (coefficient higher than 0.8). The correlation of threonine-n-propanol, leucine-isoamyl alcohol, phenylalanine-phenylethanol, glucose-n-propanol, and glucose-isobutanol varied among the rice wines made from ten rice. RT-qPCR analysis on five target genes verified the variation caused by different rice. This study for the first time reported the special formation pattern of higher alcohols during rice wine fermentation, emphasizing the early contribution of glucose metabolism on the formation of isobutanol. This study highlighted the significance of rice selection for making rice wine with good quality, and provided theoretical references for the control of higher alcohols especially in the former period during of rice wine fermentation.